Analisis Metode Guru dalam Pengembangan Karakter Disiplin AUD - Syisva Nurwita; Ranny Fitria Imran (Departement of Mathematics Education, 2023)
Character education also forms discipline. Discipline is an operative management function of all organizations including school organizations, because the better the student's discipline, the higher the learning achievement that can be achieved by them. Without good discipline, it is difficult for students to achieve optimal learning outcomes. Discipline is obedience to respect and implement a system that requires people to comply with applicable decisions, orders or regulations. In other words, discipline is compliance with the rules and regulations that have been set. Based on the problems that arise, the writer will analyze the teacher's method in developing the teacher's disciplinary character. The purpose of this research is to find out what methods teachers use in developing children's disciplinary character. The type of research conducted in this study is research that is presented in a qualitative descriptive manner. With data collection techniques using observation, interviews and documentation. Disciplinary character development for early childhood teachers can use several methods including: exemplary methods, demonstrations, field trips, inspirational stories, leadership spirit, courtesy, honesty, Inserting a Moral Message in Every Lesson, awards/appreciation. These are some of the methods that can be used in learning disciplinary character education for early childhood. These methods are complementary in nature. That is, one method with another is interconnected. This method will be able to produce a good learning, if the method is applied together. All the shortcomings and weaknesses in each of the other methods. Therefore, in order for early childhood character education learning to be successful, appropriate learning methods are able to create a good, meaningful, fun, and enjoyable learning atmosphere.